MicroRNA as a Therapeutic Target in Cardiac Remodeling. (28th September 2017) - Chen, Chao; Ponnusamy, Murugavel; Liu, Cuiyun; Gao, Jinning; Wang, Kun; Li, Peifeng
Abstract : MicroRNAs (miRNAs) are small RNA molecules that contain 18–25 nucleotides. The alterations in their expression level play crucial role in the development of many disorders including heart diseases. Myocardial remodeling is the final pathological consequence of a variety of myocardial diseases. miRNAs have central role in regulating pathogenesis of myocardial remodeling by modulating cardiac hypertrophy, cardiomyocytes injury, cardiac fibrosis, angiogenesis, and inflammatory response through multiple mechanisms. The balancing and tight regulation of different miRNAs is a key to drive the cellular events towards functional recovery and any fall in this leads to detrimental effect on cardiac function following various insults. In this review, we discuss the impact of alterations of miRNAs expression on cardiac hypertrophy, cardiomyocytes injury, cardiac fibrosis, angiogenesis, and inflammatory response. We have also described the targets (receptors, signaling molecules, transcription factors, etc.) of miRNAs on which they act to promote or attenuate cardiac remodeling processes in different type cells of cardiac tissues.